Molecular pathology of thymomas: implications for diagnosis and therapy - Marx, Alexander; Belharazem, Djeda; Lee, De-Hyung; Popovic, Zoran V.; Reißfelder, Christoph; Schalke, Berthold; Schölch, Sebastian; Ströbel, Philipp; Weis, Cleo-Aron Thias; Yamada, Yosuke (Virchows Archiv, 2021)
Thymomas exhibit a unique genomic landscape, comprising the lowest on average total mutational burden among adult human cancers; a unique point mutation in the GTF2I gene in WHO type A and AB thymomas (and rarely others); almost unique KMT2A-MAML2 translocations in rare WHO type B2 and B3 thymomas; a unique YAP1-MAML2 translocation in almost all metaplastic thymomas; and unique miRNA profiles in relation to GTF2I mutational status and WHO histotypes. While most thymomas can be diagnosed solely on the basis of morphological features, mutational analyses can solve challenging differential diagnostic problems. No molecular biomarkers have been identified that predict the response of unresectable thymomas to chemotherapy or agents with known molecular targets. Despite the common and strong expression of PDL1 in thymomas, immune checkpoint inhibitors are rarely applicable due to the poor predictability of common, life-threatening autoimmune side effects that are related to the unrivaled propensity of thymomas towards autoimmunity.
Gesehen am 12.05.2021